THE ROLE OF INTEREST IN THE CONSCIOUS CHOICE OF PROFESSION - N.Majidov; J.Majidov; B.Majidov (Scholar Express Journals, 2022)
This article deals with the role of interest in the conscious choice of a profession. In the conscious choice of a profession, an important role is played by a deep and stable interest in the profession and specialty.
Keywords: Interest; choice; profession; qualities